Electroporation Enhances the Anticancer Effects of Novel Cu(II) and Fe(II) Complexes in Chemotherapy‐Resistant Glioblastoma Cancer Cells. Issue 2 (16th January 2023) - Alkis, Mehmet Esref; Buldurun, Kenan; Alan, Yusuf; Turan, Nevin; Altun, Ayhan
Abstract: Schiff base ligand (L) was obtained by condensation reaction between 4‐aminopyrimidin‐2(1 H )‐one (cytosine) with 2‐hydroxybenzaldehyde. The synthesized Schiff base was used for complexation with Cu(II) and Fe(II) ions used by a molar (2 : 1 mmol ration) in methanol solvent. The structural features of ligand, Cu(II), and Fe(II) metal complexes were determined by standard spectroscopic methods (FT‐IR, elemental analysis, proton and carbon NMR spectra, UV/VIS, and mass spectroscopy, magnetic susceptibility, thermal analysis, and powder X‐ray diffraction). The synthesized compounds (Schiff base and its metal complexes) were screened in terms of their anti‐proliferative activities in U118 and T98G human glioblastoma cell lines alone or in combination with electroporation (EP). Moreover, the human HDF (human dermal fibroblast) cell lines was used to check the bio‐compatibility of the compounds. Anti‐proliferative activities of all compounds were ascertained using an MTT assay. The complexes exhibited a good anti‐proliferative effect on U118 and T98G glioblastoma cell lines. In addition, these compounds had a negligible cytotoxic effect on the fibroblast HDF cell lines. The use of compounds in combination with EP significantly decreased the IC50 values compared to the use of compounds alone (p<0.05). These results show that newly synthesized Cu(II) and Fe(II) complexes can be developed for use in the treatment of chemotherapy‐resistant U118 and T98G glioblastoma cells and that treatment with lower doses can be provided when used in combination with EP. Abstract :